Transport à propulsion humaine. Human powered transport. - (:unkn) unknown (My University, 2008)
Human powered transport provides vital mode not only for recreational but also for other purposes such as work, shopping and in some instances for inter-urban travel. Walking and cycling are the most common forms of sustainable, non motorised transport in the world. The human powered transport still makes a significant contribution to transport all over the world, particularly in developing countries. Human powered transportation may include the following forms: - walking; including roller blades, skateboards, non motorised scooters; - cycling; including rickshaws (and other cycle taxis) Human powered transport modes are also the most economical form of transport as they cost less than 1 eurocent per kilometre. Human powered transport modes require minimum space both in terms of road space as well as parking area. Most of the human powered transport modes are good for people s health, especially for those who are required to spend a major part of their daily job at their desk and for schoolchildren. To explain the different bicycle usages and walking patterns, the usage of human powered modes in 20 different cities were compared by distributing a questionnaire. To obtain further information about bicycle use and walking, a second questionnaire survey was carried out in 6 of the originally selected cities.
Keywords: Fahrradverkehr; Fußgängerverkehr; Autoverkehr; Gesundheit; Umwelt; Wirtschaft; Verkehrssicherheit; Distanz; Befragung; Vergleich; Individualverkehr; Fahrradnutzung; Radverkehrsanlage; Fahrradstreifen; Fahrradinfrastruktur; Fahrradabstellanlage; Fahrradmitnahme; Nachhaltigkeit